Foreign Investment and the Middle Income Trap in Southeast Asia - David Henley (Lembaran Sejarah, 2018)
This article focuses on the post-colonial catch-up by Southeast Asian nations with developed countries. The article offers an analysis of the nature and causes of the middle income trap in Southeast Asia. It discusses various interpretations of this concept, concluding with the dichotomy between laissez-faire and interventionist development strategies. Empirical evidence is provided from the automotive industry in Malaysia and Thailand. Two rival explanations of the lack of strong interventionist policies in Southeast Asia are given, one stressing the weakness of political pressure on national governments, the other linked up with historical patterns of ethnic specialization and division. The argument draws on secondary sources and reflects on implications for the study of Indonesian economic history in the colonial era.